Novel Colorimetric Sensor for Cupric Reducing Antioxidant Capacity (CUPRAC) Measurement. (2016) - Krylova, E.; Gavrilenko, N.; Saranchina, N.; Gavrilenko, M.
Abstract: A novel optic sensor was developed for screening the total antioxidant capacity based on the use of cupric – neocuproine (Cu(II)−Nc) immobilized into a polymethacrylate matrix (PMM) with spectrophotometric measurement. The absorption change associated with the formation of the colored Cu(I)−Nc chelate in the PMM as a result of reaction with antioxidants was measured at 450nm. The colorimetric CUPRAC sensor can be used for quantitative assessment of total antioxidant capacity of complex matrices such as food extracts. The sensor is small and cheap, suitable to fit in a portable instrument for in situ antioxidant analysis.